The value of school choice opportunities - Lukas Hörnig; Max Schäfer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
In this paper, we study the house price effects of local school choice opportunities among public primary schools using a rare and large-scale reform that abolished binding catchment areas in North RhineWestphalia, the largest German state with 18 million inhabitants. To estimate the reform's effect on valuations of houses, we compare houses with different local school choice sets, before and after the reform. We find that gaining access to a school within 2,000 meters and with a higher transition rate to the academic track (relative to the initial neighborhood school) increases house prices by 1.5 percent. This effect is larger when the more attractive school is closer and diminishes as distance grows. The full reform effect materializes roughly five years after reform onset.
Keywords: I28; R21; R3; 330; School choice; housing demand; real estate markets